Cellular senescence in the response of HR+ breast cancer to radiotherapy and CDK4/6 inhibitors - Vanessa Klapp; Aitziber Buqué; Norma Bloy; Ai Sato; Takahiro Yamazaki; Xi Kathy Zhou; Silvia C. Formenti; Lorenzo Galluzzi; Giulia Petroni (Journal of Translational Medicine, 2023)
Abstract Background Preclinical evidence from us and others demonstrates that the anticancer effects of cyclin-dependent kinase 4/6 (CDK4/6) inhibitors can be enhanced with focal radiation therapy (RT), but only when RT is delivered prior to (rather than after) CDK4/6 inhibition. Depending on tumor model, cellular senescence (an irreversible proliferative arrest that is associated with the secretion of numerous bioactive factors) has been attributed beneficial or detrimental effects on response to treatment. As both RT and CDK4/6 inhibitors elicit cellular senescence, we hypothesized that a differential accumulation of senescent cells in the tumor microenvironment could explain such an observation, i.e., the inferiority of CDK4/6 inhibition with palbociclib (P) followed by RT (P→RT) as compared to RT followed by palbociclib (RT→P). Methods The impact of cellular senescence on the interaction between RT and P was assessed by harnessing female INK-ATTAC mice, which express a dimerizable form of caspase 8 (CASP8) under the promoter of cyclin dependent kinase inhibitor 2A (Cdkn2a, coding for p16Ink4), as host for endogenous mammary tumors induced by the subcutaneous implantation of medroxyprogesterone acetate (MPA, M) pellets combined with the subsequent oral administration of 7,12-dimethylbenz[a]anthracene (DMBA, D). This endogenous mouse model of HR+ mammary carcinogenesis recapitulates key immunobiological aspects of human HR+ breast cancer. Mice bearing M/D-driven tumors were allocated to RT, P or their combination in the optional presence of the CASP8 dimerizer AP20187, and monitored for tumor growth, progression-free survival and overall survival. In parallel, induction of senescence in vitro, in cultured human mammary hormone receptor (HR)+ adenocarcinoma MCF7 cells, triple negative breast carcinoma MDA-MB-231 cells and mouse HR+ mammary carcinoma TS/A cells treated with RT, P or their combination, was determined by colorimetric assessment of senescence-associated β-galactosidase activity after 3 or 7 days of treatment. Results In vivo depletion of p16Ink4-expressing (senescent) cells ameliorated the efficacy of P→RT (but not that of RT→P) in the M/D-driven model of HR+ mammary carcinogenesis. Accordingly, P→RT induced higher levels of cellular senescence than R→TP in cultured human and mouse breast cancer cell lines. Conclusions Pending validation in other experimental systems, these findings suggest that a program of cellular senescence in malignant cells may explain (at least partially) the inferiority of P→RT versus RT→P in preclinical models of HR+ breast cancer.